Use intensity of progesterone devices for fixed-time artificial insemination in gyr crossbred cows from the peruvian tropics - Poclín Rojas, Annie Yoselin (2025)
Background: The implementation of routine fixed-time artificial insemination programs can generate significant waste and costs, which good management practices can help mitigate. The objective of the study was to assess the effects of second- and third-use progesterone devices on estrus characteristics and pregnancy rates in synchronized crossbred Gyr cows. Methods: Ten cows were synchronized with first-use Bovine Intravaginal Progesterone Devices (DIB), nine with second-use DIB and ten with third-use DIB. All cows were ≥90 days postpartum, had an average milk production of 6.9±1.9 L/day and were aged 4-10 years. Estrus signs were recorded at insemination and pregnancies were confirmed at 60 days by ultrasonography. Result: No significant associations were found between DIB use intensity and estrus detection patch response, mucus color, body condition score (CC), calvings, or breed purity (p>0.05). Body condition was associated with uterine turgor tone (p<0.05) and 100% of cows with CC 3.0 showed turgor tone 3. The highest pregnancy rate was found in second-use DIB (55.6%) and CC 2.8 (47.1%), though neither association was significant (p>0.05). DIBs may be used up to a second-use, as cervical mucosal stimulation and pregnancy rate remain unaffected.